ColoNav: patient navigation for colorectal cancer screening in deprived areas – Study protocol. Issue 1 (December 2016) - Allary, C.; Bourmaud, A.; Tinquaut, F.; Oriol, M.; Kalecinski, J.; Dutertre, V.; Lechopier, N.; Pommier, M.; Benoist, Y.; Rousseau, S.; Regnier, V.; Buthion, V.; et al.
Abstract Background The mass colorectal cancer screening program was implemented in 2008 in France, targeting 16 million French people aged between 50 and 74. The current adhesion is insufficient and the participation rate is even lower among the underserved population, increasing health inequalities within our health care system. Patient Navigation programs have proved their efficiency to promote the access to cancer screening and diagnosis. Methods/Design The purpose of the study is to assess the implementation of a patient navigation intervention that has been described in another cultural environment and another health care system. The main objective of the program is to increase the colorectal cancer screening participation rate among the deprived population through the intervention of a navigator to promote the Fecal Occult Blood Test (FOBT) and complementary exams. We performed a multisite cluster randomized controlled trial, with three groups (one experimental group and two control groups) for 18 months. Discussion The study attempts to give a better understanding of the adhesion barriers to colorectal cancer screening among underserved populations. If this project is cost-effective, it could create a dynamic based on peer approaches that could be developed for other cancer screening programs and other chronic diseases. Trial registration NCT02369757